Panchromatic absorption of dye sensitized solar cells by co-Sensitization of triple organic dyes. Issue 2 (6th November 2017) - Islam, Ashraful; Chowdhury, Towhid H.; Qin, Chuanjiang; Han, Liyuan; Lee, Jae-Joon; Bedja, Idriss M.; Akhtaruzzaman, Md; Sopian, Kamaruzzaman; Mirloup, Antoine; Leclerc, Nicolas
Abstract : Dye sensitized solar cells (DSSCs) were co-sensitized with three custom molecularly engineered organic dyes containing butyloxyl chain induced dye (Y1), boron dipyrromethene (bodipy) dye (TP2 A), and squaraine (SQ) ring configured dye (HSQ4). Abstract : Dye sensitized solar cells (DSSCs) were co-sensitized with three custom molecularly engineered organic dyes containing butyloxyl chain induced dye (Y1), boron dipyrromethene (bodipy) dye (TP2 A), and squaraine (SQ) ring configured dye (HSQ4). The individual power conversion efficiencies of the DSSCs sensitized with Y1, TP2 A and HSQ4 sensitizers were 3.44%, 4.26% and 5.78%, respectively. Co-sensitized TP2 A + HSQ4 dyes at a 2 : 1 molar ratio showed an efficiency of 7.02%. Further addition of Y1 dye with optimal TP2 A + HSQ4 increased the V OC from 0.580 V to 0.605 V. The co-sensitized Y1 + TP2 A + HSQ4 based DSSCs showed a new optimal efficiency ( η ) of 7.48%. This is the highest efficiency recorded for DSSCs based on co-sensitization of triple organic dyes. Intensity modulated photovoltage spectroscopy further confirms the longer lifetime of co-sensitized Y1 + TP2 A + HSQ4 compared to that of each individual TP2 A and HSQ4 and co-sensitized TP2 A + HSQ4 dye.